2022
DOI: 10.2147/ijgm.s347439
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Nursing Interventions Based on Pygmalion Effect Could Alleviate Negative Emotions of Patients with Suspected COVID-19 Patients: a Retrospective Analysis

Abstract: Purpose: This study aims to explore the psychological status of suspected COVID-19 patients during quarantine and put forward a new yet effective psychological nursing strategy for intervention. Patients and Methods:We performed a retrospective study with suspected COVID-19 patients who were hospitalized to the two hospitals of Hunan province, China and accepted the intervention of psychological nursing from 01/2020 to 03/2020. The control group received routine psychological nursing care and the observation g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It is a new nursing model. Expectation-action-acceptance in the process of internalization, positive psychological hints are given by affirmation and encouragement, to achieve the purpose of adjusting the physical and mental state [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a new nursing model. Expectation-action-acceptance in the process of internalization, positive psychological hints are given by affirmation and encouragement, to achieve the purpose of adjusting the physical and mental state [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that there is a lack of clarity in the division of labor between departments and duplication of investigations by various departments in the process of epidemiological investigation.. It is recommended that the relevant departments should strengthen the integration and sharing of information by using big data and increase training in epidemiological investigation to improve efficiency 26 . Knowing the benefits of epidemiological investigation and personal information protection can reduce the uneasiness of infected patients, it is recommended that the media increase the scientific knowledge of epidemiological investigations and, at the same time, hide patients’ last names in the publication of epidemiological investigation information to protect the privacy of infected patients, and prohibit malicious human searches and other behaviors.…”
Section: Discussionmentioning
confidence: 91%
“…Healthcare workers who are fully "armed" can paste their names on their protective clothing to improve communication between doctors and patients and reduce patients' sense of isolation. There are also studies 26 suggesting the use of the Rosenthal effect, that is, using praise, trust and expectation, and other psychological hints to help patients regain confidence and obtain positive motivation to change their own behaviors. By communicating with patients to understand their psychological needs, sources of negative emotions and specific factors affecting their emotions, healthcare professionals, in collaboration with teams from various disciplines, can encourage infected patients to cope positively and provide social support and psychological guidance to improve their quality of life 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The Pygmalion effect refers to a psychological phenomenon in which beliefs or expectations that are expected to lead to the occurrence of an outcome make that outcome more likely to occur .In a healthcare setting, the attitudes, words, or actions of doctors, nurses, or other healthcare professionals toward patients or the care they provide may affect patients' expectations, which in turn may affect treatment outcomes or the recovery process.The Pygmalion effect has attracted a great deal of research effort, part of which seeks to gain insights into the interactions between patients, physicians, and the healthcare environment in order to optimize medical practice and improve patient outcomes. For example, patients with suspected COVID − 19 tend to exhibit symptoms of depression, anxiety, and irritability during quarantine, and psychological care based on the Pygmalion effect can help alleviate their negative emotions [47].In examining the Pygmalion effect in nursing home caregiver expectations on patient prognosis [27].The application of the Pygmalion effect intervention model to elderly patients with COPD and lung infections promotes clinical regression, improves their pulmonary function and quality of life, and thus enhances satisfaction with care [26]It is believed that the Pygmalion effect, when applied to breast cancer patients during surgery, can improve their psychological resilience, enhance their belief in healing, effectively improve their treatment compliance, and J.Y.Kim et allead to a rapid recovery from the disease, which is worthy of popularization and application [24]. A systematic evaluation revealed different domains of doctor-patient relationship and communication with convincing effects on different objective and subjective health outcomes [38].…”
Section: Related Researchmentioning
confidence: 99%